2020
DOI: 10.1038/s41587-020-0438-y
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel interrogation and mining of natively paired human TCRαβ repertoires

Abstract: T cells engineered to express antigen-specific T cell receptors (TCRs) are potent therapies for viral infections and cancer. However, efficient identification of clinical candidate TCRs is complicated by the size and complexity of T cell repertoires and the challenges of working with primary T cells. Here, we present a high-throughput method to identify TCRs with high functional avidity from diverse human T cell repertoires. The approach uses massively parallel microfluidics to generate libraries of natively p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 66 publications
1
52
0
Order By: Relevance
“…However, especially the identification and in‐depth characterisation of suitable TCRs for clinical use was so far a tedious process and only a handful of clinical studies with TCR re‐directed T‐cell products are reported 5–9 . Today, because of continuous improvements in the field of next‐generation sequencing, high‐throughput identification of full αβ TCR sequences is no longer a bottleneck 10–13 . Moreover, advanced bioinformatical analytical tools are developed to gain deep insight into such large TCR repertoire data and to predict antigen‐HLA specificity from raw TCR sequences 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…However, especially the identification and in‐depth characterisation of suitable TCRs for clinical use was so far a tedious process and only a handful of clinical studies with TCR re‐directed T‐cell products are reported 5–9 . Today, because of continuous improvements in the field of next‐generation sequencing, high‐throughput identification of full αβ TCR sequences is no longer a bottleneck 10–13 . Moreover, advanced bioinformatical analytical tools are developed to gain deep insight into such large TCR repertoire data and to predict antigen‐HLA specificity from raw TCR sequences 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…First, input linked scFv repertoires typically comprised approximately 2- to 4-fold more antibodies than the final CHO cell banks. Our prior work to clone T cell receptor (TCR) repertoires into Jurkat cells was much more efficient, 43 but that work used lentivirus rather than Flp-In site directed integration, and therefore many Jurkat clones expressed multiple TCRs. In the future, we will work to improve the efficiency of CHO engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Fast and inexpensive functional screening of transiently expressed TCRs in CD8+ and CD4+ Jurkats has been established, but the transient nature prevented further engineering approaches and selections. Current research in the field has been overwhelmingly focused on affinity-based selections of TCRs ( Kessels et al., 2001 ; Chervin et al., 2008 ; Malecek et al., 2013 ; Schmitt et al., 2017 ; Wagner et al., 2019 ; Spindler et al., 2020 ). As highlighted in previous sections, affinity maturation of scTCR-pMHC pairs has been done by phage and yeast display screening.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports demonstrate the use of mammalian cells for TCR screening and engineering, most of which involved viral transformations and affinity-based selections ( Kessels et al., 2001 ; Chervin et al., 2008 ; Malecek et al., 2013 ; Schmitt et al., 2017 ; Wagner et al., 2019 ; Spindler et al., 2020 ). In order to overcome the challenges related to TCR affinity and cross-reactivity, it is necessary to engineer TCR specificity not only on the basis of binding and function ( Rosskopf et al., 2018 ), but also while detecting cross-reactivity.…”
Section: Introductionmentioning
confidence: 99%